The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/jora.12112
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Effects of Fathers' Depressed Mood on Youth Internalizing Symptoms in Early Adulthood

Abstract: While an accumulating body of research has documented increased risk for psychopathology among children of depressed fathers, most studies have used cross-sectional design and little is known about offspring outcomes beyond childhood. Using prospective data from a community sample (N = 395), we found that paternal depressive symptoms when children were in early adolescence (age 13) predicted offspring depressive and anxiety symptoms at age 21, controlling for baseline youth symptoms, maternal depressive sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 136 publications
(115 reference statements)
3
37
0
2
Order By: Relevance
“…Although most studies focus on mothers, exposure to paternal depression may also pose a risk to offspring wellbeing. Reeb et al (2015) observed that exposure to paternal depressive symptoms at age 13 predicted depressive and anxiety symptoms at age 21, regardless of baseline symptoms and maternal depressive symptoms. These results were in line with reviews on paternal psychiatric disorders and child psychosocial development (Ramchandani and Psychogiou, 2009;Spector, 2006) as well as other studies on paternal depression as a risk factor for offspring depression and internalizing problems (Bögels and Phares, 2008;Kane and Garber, 2009).…”
Section: Introductionmentioning
confidence: 67%
“…Although most studies focus on mothers, exposure to paternal depression may also pose a risk to offspring wellbeing. Reeb et al (2015) observed that exposure to paternal depressive symptoms at age 13 predicted depressive and anxiety symptoms at age 21, regardless of baseline symptoms and maternal depressive symptoms. These results were in line with reviews on paternal psychiatric disorders and child psychosocial development (Ramchandani and Psychogiou, 2009;Spector, 2006) as well as other studies on paternal depression as a risk factor for offspring depression and internalizing problems (Bögels and Phares, 2008;Kane and Garber, 2009).…”
Section: Introductionmentioning
confidence: 67%
“…Consistent with these findings, our results indicated that maternal depressive symptoms predicted increased adolescent depressive symptoms for girls but not for boys. The findings regarding the impact of paternal depression are mixed, with studies reporting a stronger influence on girls (Reeb and Conger 2009; Reeb et al 2015), a stronger influence on boys (Eberhart et al 2006), or a comparable influence across gender groups (Currier et al 2006; Pettit et al 2008). Here, results supported the latter by failing to reveal gender moderation in the pathway from paternal depressive symptoms to increased adolescent depressive symptoms; the positive association was comparable for boys and girls.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, depression in fathers does appear to increase the risk for depressive symptoms in children (Connell and Goodman 2015; Kane and Garber 2015; Phares and Compas 1992; Wilson and Durbin 2010), although some exceptions to this finding do exist (Agerup et al 2015; Tully et al 2008). Among studies that have directly compared the effects of maternal and paternal depression, the findings tend to show that the magnitude of effects from mothers and fathers is comparable (Reeb and Conger 2009; Reeb et al 2015). Given the relative lack of attention to understanding the consequences of paternal versus maternal depression and mixed findings in existing studies, there is a pressing need for additional research that includes both fathers and mothers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we control for fathers' and mothers' self-reports of their involvement in daily activities with the child, including routine caregiving and play. We control for symptoms of depression as well as parenting stress and alcohol consumption because studies of mothers (Farmer & Lee, 2011;Silverstein, Augustyn, Young, & Zuckerman, 2009;Taylor, Guterman, Lee, & Rathouz, 2009) and fathers (Davis, Davis, Freed, & Clark, 2011;Lee, Perron, Taylor, & Guterman, 2011;Reeb et al, 2014;Wilson & Durbin, 2010) have linked these factors to poorer parenting and physical punishment of young children. Furthermore, maternal distress and depression (Ciciolla, Gerstein, & Crnic, 2013;Goodman et al, 2011;Taylor, Manganello, Lee, & Rice, 2010) are direct and mediating factors linked to the development of child aggression.…”
Section: The Current Studymentioning
confidence: 99%